The Positive and Negative Politeness Strategies by the Characters Every Waking Breath Movie - Febri Aspitasari; Made Budiarsa; Gede Primahadi Wijaya Rajeg (Humanitatis : Journal of Language and Literature, 2022)
Abstract Good communication happened when a message is delivered by the speaker is well received by the interlocutor and both the speaker and the interlocutor feel good about what they do together. Thus make politeness and language cannot be separated. Politeness is not only can be seen from the manner, but also from the use of language. Positive and negative politeness strategies are commonly applied by people in their communication process. By understanding these two strategies, people are able to interact better in society. This study investigates how positive politeness and negative politeness strategies are enacted by the characters in the Every Waking Breath movie, and which strategies are predominantly applied. The data was taken from the characters’ utterances. Documentation and observation method were used and was assisted by note-taking techniques to obtain the data. Mix-method was used to present the analysis. The results showed there are nine types of positive politeness strategies applied by the characters, (i.e., Abigail/ Liz, Mark, and Sophie). The predominant positive politeness strategy used is Strategy 4: [Use in-group identity markers]. On the other hand, we identified five types of negative politeness strategies applied by characters. The conclusion of this research is that 17 (70,83%) of the total 24 utterances evoke the positive politeness strategies while 8 (29,17%) reflect the negative politeness strategies. The predominance of the positive politeness strategies suggests socially close relationships and solidarity between interlocutors in the movie. Keywords: Politeness Strategies, Positive Politeness Strategies, Negative Politeness Strategies, Movie, Characters.